Antibiotic Resistance Dynamics and Isolation Rate of Staphylococci and Enterococci from Patients of Reconstructive Surgery Units - N. S. Bogomolova; L. V. Bolshakov; S. M. Kuznetsova; T. D. Oreshkina (Антибиотики и Химиотерапия)
The dynamics of isolation of staphylococci and enterococci from clinical material of patients and their antibiotic susceptibility within a 5-year period (2005-2009) was analysed. 5990 isolates were tested: 1250 isolates of Staphylococcus aureus, 3268 isolates of S.epidermidis, 1005 isolates of Enterococcus faecalis and 467 isolates of E.faecium. Grampositive infections were shown to be prevailing within the last 2-3 years, the nosocomial epidermal staphylococci more and more replacing S.aureus (the ratio of S.epidermidis and S.aureus in 2009 was 3.3). The isolation rate of E.faecalis significantly increased (by 3.5 times) and the ratio of E.faecalis and E.faecium in 2009 was 4.3. The microflora composition with respect to the isolation source was analysed and its clinical significance was estimated. The study of the antibiotic susceptibility showed that oxacillin had its own specific niche, while antibiotics active against resistant grampositive cocci, such as rifampicin, fusidic acid, fluoroquinolones (moxifloxacin), cefoxitin, as well as amoxicillin/clavulane in infections due to E.faecalis, might be considered as the drugs of choice. In the treatment of nosocomial infections, when the etiological role of MRSA or VRE is suspected or confirmed, the complex therapy should obligatory include the most active antibiotics (vancomycin or linezolid among them).